Functional Group And Phytochemical Properties Detection Of Peperomia Pellucida Leaves Extract - Nurul Syamimi Norisham; Faiqa Husna Mohamad Mulfazir; Muhammad Zulfikar Firas Putra Zulpakar; Luqman Nur Hakim Paharudin; Ahmad Hakimi Shaffie; Liyana Amalina Adnan; Ehwan Ngadi; Rahayu Ahmad (ASIAN SCHOLARS NETWORK, 2024)
Asian Journal of Fundamental and Applied Sciences, Volume 4 Issue 4 Page (1–9)